Analisis TAM Terhadap Sikap Penggunaan Sistem Informasi Akuntansi Penggajian di PT Garuda Indonesia Station DPS - Vidantika, Putu Nanda Christy Dio; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p11, 2018)
A well-implemented accounting information system (AIS) can provide a reliable financial information for company. The use of technology on AIS for the payroll business process should consider usefulness and easiness of its users so the system becomes effective. This study was aimed to examine the effect of perceived usefulness (PU) and perceived ease of use (PEOU) toward attitude towards use (ATU) as an acceptance indicator of technology. The research was conducted at PT Garuda Indonesia Station DPS. The samples as many as 68 peoples were selected by nonprobability sampling method. The data were collected by using survey, observation, interview, and literature study. The analysis technique used the multiple linear regression analysis. The result showed that PU and PEOU positively influence ATU of technology on AIS for payroll business process. This showed that the more useful and easy technology of SIA for payroll is, the acceptance of technology will be better. Keywords: attitude towards use, perceived usefulness, perceived ease of use, AIS